Probability of Erroneous Data Registration in a Single Photon Erasure-Type Communication Channel with a Receiver Based on a Photon Counter - A. M. Timofeev (Приборы и методы измерений)
When measuring low-power optical signals, it is necessary to ensure the highest reliability of the received data, which is especially important for single-photon communication channels. This determines the expediency of using photon counters as receiving modules for such channels. They are highly sensitive, but are characterized by data recording errors. Therefore, the purpose of this work was to investigate the influence of the intensity of the registered optical radiation J0 during the transmission of binary symbols “0” on the probability of registering symbols “1” at the output of the communication channel in the presence of symbols “0” at its input P(1/0).The statistical distributions of the mixture of the number of dark and signal pulses at the output of the photon counter during the registration of binary symbols “0” Pst0 (N ) were determined. To do this, a technique was used to reduce information loss. As a result, the minimum probability P(1/0) was reached.The probabilities P(1/0) were calculated for a communication channel containing a photon counter as a receiving module. This calculation was carried out at different values of the supply voltage of the avalanche photodetector U and the intensity of the optical signal used to transmit the binary symbols “0” J0 .The experimental results showed that with increasing optical signal intensity J0 , the dependences P(1/0) on J0 initially remain almost unchanged and retain a constant value. However, with a further increase in J0 , there is a linearly increasing character of the dependences P(1/0) on J0 . Moreover, with other equal reception parameters, such a character of the dependences P(1/0) on J0 begins to manifest itself at higher intensities of the optical signal J0 with an increase in the supply voltage of the avalanche photodetector.